Development of the hardware for a vehicle smart alarm system - Goh, Beng Fong (2016)
Road safety has often been neglected and thus the Vehicle Alarm System is created to suit such needs on the road. The Vehicle Alarm System allows the driver to be alerted on the road and prompts an alarm whenever danger arises on the road. It serves as a self-enforcing tool to the driver, where the driver’s android phone connects to the Arduino board through Bluetooth and the alarm on the android phone is activated whenever a situation leading to an accident occurs. With this tool, drivers are able to focus their attentions on the road and be alert of their surroundings, leading to safe driving on the road and lower death rates on the road. Efforts are ongoing for further improvisation to enhance the aesthetics of the car with the Vehicle Alarm System mounted on it and to improve the efficiency of the system.